SICKNESS PRESENCE AND STRESSFUL LIFE EVENTS OF HEALTH CARE WORKERS - Škerjanc, Alenka; Fikfak, Metoda Dodič (Central European journal of public health, 2015)
AIM: The aim of the study is to investigate the relationship between sickness presence and stressful life events among health care workers. METHODS: Data were gathered from all health care workers at the University Medical Centre Ljubljana employed there in the period between 1 January 2010 and 31 December 2010. Each employee obtained a questionnaire composed of two standardized international questionnaires. RESULTS: There were 57% of sickness present health care workers among the participants. The sickness present reported to have more diseases of family member than the non-sickness present (OR = 1.5; 95% CI = 1.2-2.0), loan (OR = 1.4; 95% CI = 1.1-1.6), their partner lost job (OR = 1.4; 95% CI = 1.0-1.8), or they changed the place of living (OR = 1.4; 95% CI = 1.0-2.0). CONCLUSIONS: The results of the study indicate that stressful life events with economic consequences might have an important influence on sickness presence.
Keywords: Socioeconomic Factors; Male; Presenteeism; životní změny; Health Personnel; presenteismus; sexuální faktory; psychický stres; Adult; Age Factors; socioekonomické faktory; dospělí; mužské pohlaví; Exercise; Smoking; zdravotnický personál; lidé; Life Change Events; ženské pohlaví; Humans; Stress, Psychological; Sex Factors; věkové faktory; Female; cvičení; lidé středního věku; kouření; Middle Aged